A New-Sociologist Makes Peace with One of his Former Subconscious Role Models - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
This presentation contains extracts from the correspondence between a former-engineer Turkish sociologist and a foreign sociology instructor, with whom he had befriended years ago. At the time, the Turkish sociologist was an engineering student and as such, he used to underestimate sociology. Moreover; he did not even refrain from expressing this openly in his conversations. Years later, though, he wants to find the address of that instructor (now an emeritus professor) and in a sense submit his apology; because, now, let alone appreciating sociology, he himself has obtained a Ph.D. degree in sociology; in the mean time. The need to establish such a dialogue is a compulsory task of reliving his conscience as it would come equal to a professional debt and an ethical self-acquittal. (C) 2015 The Authors. Published by Elsevier Ltd. This is an open access article under the CC BY-NC-ND license.
Keywords: Sociology; individual; empathy; culture; Ph.D. degree